Dissolution Of Natural Fiber Using Ionic Liquid For Production Of Cellulose Nanoparticles - Yahya, Nadzirah (2014)
Natural fiber (NF) exhibits desirable properties such as renewability, biodegradability, environment-friendly, lightweight, low density, high specific mechanical performance, good electrical and thermal conductivities, and low cost. Cellulose nanoparticles (CNPs) embedded in NF possess even greater properties caused by the high crystallinity of cellulose fiber. In this study, dissolution process was used in order to extract these CNPs from NF source; coconut fiber (CF). The process was done using an ionic liquid (IL) 'green solvent' that are best known for their capabilities in chemical reaction and extraction! separation processes. IL is known to be non-volatile, non-flammable, and recyclable, with low toxicity and vapor pressure. The properties of CNPs extracted was further determined using fourier transform infrared (FTIR) analysis, thermogravimetric analysis (TGA), scanning electron microscope (SEM) analysis, high resolution thermal electron microscope (HRTEM) analysis and dynamic light scattering (DLS) analysis. An optimization studies on the ultrafine CNPs extraction resulted in an optimum operating condition of 74.90min, 10S.06°C and O.OS wt% of CF:IL.